Who is aware of circularity? Firm-level survey evidence from Uganda - Klaus S. Friesenbichler; Ina Meyer (Austrian Institute of Economic Research (WIFO), 2024)
This paper studies the distribution of knowledge about the circular economy as a business concept. Knowledge about circularity is a prerequisite for the diffusion of innovation onto which the incorporation of more circularity into economic processes hinges. We study the economic factors affecting the distribution of knowledge across firms. Using novel survey data from Uganda, we present empirical evidence of circularity in a developing country context. In line with the resource-based view of the firm, the findings indicate that larger and more productive firms, and firms with proactive business strategies, are more likely to be informed about the circular economy. Exposure to environmental barriers, such as adverse climate change impacts or high energy intensity, is not related to the awareness of circularity. The findings suggest that policy makers should improve environmental regulations, inform entrepreneurs about opportunities in circular business models and facilitate the establishment of a waste sector to demonstrate a step towards implementation of circular economy principles.
Keywords: Q53; Q56; N57; 330; circular economy; innovation; diffusion; awareness; Uganda; firm; survey; resource-based view